Effects of the Pilates method isolated and associated with manual therapy in women with urinary incontinence - Gordon, Stephany; Ruivo, Daniele Bastos; Viscardi, Luciana Gonzalez Auad; Oliveira, Adriana Sarmento de (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Urinary incontinence (UI) is clinically defined by the International Continence Society as involuntary urine loss. Currently, UI is considered a public health issue worldwide, considering that the prevalence in women is quite high, requiring attention from health professionals. Objective: To evaluate the effects of the Pilates method associated with Manual Therapy in women with UI. Methods: It was performed a randomized, controlled, longitudinal clinical trial with a quantitative approach of the data. 14 female participants were evaluated, aged 20 to 55 years and who had presented episodes of urinary loss in the last months. The following evaluations were carried out: anamnesis, evaluation of urogynecological history, application of the King’s Health Questionnaire and PERFECT test. After all the evaluations, half of the volunteers received treatment for urinary incontinence through a physical therapy approach that includes the Pilates method associated with Manual Therapies (GPT), and the other half received treatment using only the Pilates method (GP). Results: Both groups showed increased PFM strength, being GPT (p = 0.04) and GP (p = 0.00); increased resistance, being GPT (p = 0.02) and GP (p = 0.01); and the contraction of fibers, being GPT (p = 0.04) and GP (p = 0.02). In the GPT there was a decrease in the severity measures (p = 0.01); disappearance of nocturia (p = 0.04); decreased symptoms of SUI (p = 0.02); and bladder pain (p = 0.04). In the GP, there was a significant improvement in the perception of health (p = 0.00); decreased UI impact on the participant's life (p = 0.02); the influence of UI on emotions (p = 0.00); symptoms of overactive bladder (p = 0.01); and the SUI (p = 0.00). Conclusion: Both treatment protocols decrease episodes of leakage of urine when there is an increase in intra-abdominal pressure, increase the PFM strength, endurance and number of fast contractions, and the quality of life of women with UI. However, only the group that received only the Pilates protocol showed an increase in repetitions of slow contraction.